Beachrock as sea-level indicator – A case study at the coastline of Oman (Indian Ocean). (15th February 2019) - Falkenroth, M.; Schneider, B.; Hoffmann, G.
Abstract: Future sea level changes are a threat to coastal communities worldwide. Therefore, reliable methods for the reconstruction of past relative sea-level variations are essential to make predictions of future developments. Beachrocks are a widely distributed indicator of Quaternary paleo-coastlines, with a high potential for preservation. Nevertheless, their use as sea-level indicator faces challenges in the determination of the exact elevation of beachrock formation with respect to paleo sea level. This information is crucial to the establishment of a sea-level index point. Our study area on the northeastern coastline of Oman shows a set of twelve marine terraces that reach a height of 500 m above mean sea level. While the upper terraces are erosional, the lowest three are depositional. On the erosional terraces beachrocks are the only sediment-cover that withstood erosion. On the depositional terraces however, beachrocks occur alongside other sediments, which can be fluvial, alluvial, or marine in origin. The coastal development of the area is of high interest as uplift and tectonic activity are ongoing. Fieldwork and petrographic methods on eight outcrops on three terrace levels led to the identification of eight lithofacies in six facies associations. We used facies analysis to improve the information on paleo sea level as derived by the sole use of geomorphological indicators. Here, we demonstrate that facies analysis (so far applied exclusively on sandy deposits) is applicable also to gravel-dominated systems. The results contribute to knowledge on local changes in the depositional environment and help to reconstruct uplift rates. Highlights: Facies analysis can improve the accuracy of beachrocks as sea-level indicator. Six distinct lithofacies were identified in sand- and gravel-dominated beachrocks. The method requires a certain thickness and well preserved beachrocks. Berm and breaking depth are not always adequate limits of beachrock-formation.